Annual dialysis data report 2020, JSDT renal data registry - Norio Hanafusa; Masanori Abe; Nobuhiko Joki; Junichi Hoshino; Kan Kikuchi; Shunsuke Goto; Eiichiro Kanda; Masatomo Taniguchi; Shigeru Nakai; Toshihide Naganuma; Takeshi Hasegawa; Kenichiro Miura; et al. (Renal Replacement Therapy, 2024)
Abstract Background The 2020 Japanese Society for Dialysis Therapy Renal Data Registry (JRDR) annual survey was sent to 4493 dialysis facilities in Japan. Methods Questionnaires were sent to all facilities that provide patients with dialysis therapy in Japan. Data were collected and compiled to form cross-sectional results of renal replacement therapy from various aspects. Results In total, 4437 facilities (98.8%) responded to the facility questionnaire and 4271 (95.1%) responded to the patient questionnaire. The number of chronic dialysis patients in Japan continues to increase every year, reaching 347,671 at the end of 2020 and giving a prevalence rate of 2754 patients per million population. The mean age was 69.40 years. Diabetic nephropathy was the most common primary disease among the prevalent dialysis patients (39.5%), followed by chronic glomerulonephritis (25.3%) and nephrosclerosis (12.1%). There were 40,744 incident dialysis patients during 2020, representing a decrease of 141 from 2019. The average age of patients on dialysis was 70.88 years, with diabetic nephropathy being the most common underlying disease (40.7%) second most common was nephrosclerosis (17.5%), which was unchanged from the previous year and surpassed chronic glomerulonephritis (15.0%). There were 34,414 patient deaths in 2020; the crude mortality rate was 9.9%. The main causes of death were heart failure (22.4%), infection (21.5%), and malignancy (9.0%), which were almost the same as the percentages for the previous year. Since 2012, the number of patients treated by hemodiafiltration has increased rapidly; in 2020, the number of patients on this modality was 163,825, accounting for 47.1% of all patients on maintenance dialysis. The number of patients on peritoneal dialysis has been on the rise since 2017, reaching 10,338 in 2020; 20.8% of whom received combined therapy with hemodialysis or hemodiafiltration, showing no change from the previous year. A total of 751 patients were on home hemodialysis at the end of 2020, representing a decrease of 9 from the end of 2018. In 2020, coronavirus disease 2019 (COVID-19) infection and malignancy were added as new items in the survey. Continuing on from the 2019 survey, history of kidney donation for a living-donor transplant was investigated. Conclusions Present issues and challenges in renal replacement therapy were identified in the responses to the new questionnaire items included in this survey. A more detailed evaluation with adjustment for patient background factors should clarify the characteristics of the underlying diseases and conditions in dialysis patients. Trial registration The JRDR was approved by the Japanese Society for Dialysis Therapy ethics committee. It was registered in the University Hospital Medical Information Network (UMIN) Clinical Trials Registry on 10 September 2020 and in the UMIN clinical trials registration system (UMIN000018641).